JSON Implementation to Minimize the Use of the Number of Columns of a Table in a PostgreSQL Database - Mochamad Alfan Rosid (JOINCS (Journal of Informatics, Network, and Computer Science), 2017)
On the development of the database currently has become a very important thing, each will plan something, consider any thing we will need and use existing data in a database, The development of the database currently has become a very important thing, when we want to plan something and consider everything, we will need and use existing data in a database, PostgreSQL is one Object Relational Database Management Systems (DBMS) open source with a lot of features that are not less sophisticated to commercial databases. On daily use, it sometimes occurs a case that requires a dynamic column, therefore we should make the new columns to meet those needs. However, if each row of the table column requires different column and potentially need another ones, then it is going to be useless. On the research of utilizing the technology of JavaScript Object Notation (JSON),Json_encode PHP programming language can simplify the use of the column so that a new column is no longer needed when we want to create a new column on the table, we only need a new column that stores an array that has been converted into a JSON string forms the result of json_encode that represents the column name and the content of the columns of a table.